The Notary's Right of Refusal in Examination: Study of Judicial Consideration of Decision Number 1003 K/PID/2015 - Thea Farina; Nuraliah Ali; Ruzian Markom (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Objective: This research was conducted to present considerations to the judge regarding the notary's right of refusal in the case of an examination (Study on Case Decision Number 1003 K/PID/2015) and the consequences related to the notary's right utilization according to the law on the notary's office and code of ethics in Indonesia. Methodology: This research adopted normative juridical law research, employing statute and case approaches. The materials obtained from the research findings were systematically collected and classified according to the subject matter and then qualitatively analyzed. Results: This research emphasized that the right of refusal in the position of a notary is contained in the notary oath of office, which prohibits disseminating the contents of the data. Regarding the consequences of the notary refusal, the notary will be discharged from witness obligations or a general testimony for the release of the notary from various demands related to all parties' interests. Applications of this study: The study provides a reference conceptualized into norms that can be accepted and implemented in society and become a moral guideline regarding the notary's right of refusal in the case of an examination. Novelty/Originality: This research concerns the notary's right of refusal in the examination context and its consequences. This study focuses on the judge's consideration investigation and its relation to the law on notary office and the notary code of ethics, which are relatively uncommon in Indonesia. Keywords: Notary, Right of Refusal, Law on Notary Office, Code of Ethics ABSTRAK Tujuan: Penelitian ini dilakukan untuk memberikan pertimbangan kepada hakim mengenai hak ingkar notaris dalam perkara pemeriksaan (Studi Putusan Perkara Nomor 1003 K/PID/2015) dan akibat yang terkait dengan penggunaan hak notaris menurut hukum tentang jabatan notaris dan kode etik di Indonesia. Metodologi: Penelitian ini menggunakan penelitian hukum yuridis normatif, dengan pendekatan undang-undang dan kasus. Bahan-bahan yang diperoleh dari temuan penelitian dikumpulkan secara sistematis dan diklasifikasikan menurut pokok bahasan kemudian dianalisis secara kualitatif. Hasil: Penelitian ini menegaskan bahwa hak ingkar jabatan notaris tertuang dalam sumpah jabatan notaris yang melarang penyebarluasan isi data. Mengenai akibat penolakan notaris tersebut, notaris akan dibebaskan dari kewajiban saksi atau keterangan umum untuk pembebasan notaris dari berbagai tuntutan yang berkaitan dengan kepentingan semua pihak. Aplikasi penelitian: Kajian ini memberikan acuan yang dikonseptualisasikan ke dalam norma-norma yang dapat diterima dan dilaksanakan di masyarakat serta menjadi pedoman moral mengenai hak ingkar notaris dalam hal pemeriksaan. Kebaruan/Orisinalitas: Penelitian ini menyangkut hak ingkar notaris dalam konteks pemeriksaan dan akibatnya. Kajian ini berfokus pada pemeriksaan pertimbangan hakim dan kaitannya dengan undang-undang jabatan notaris dan kode etik notaris yang relatif jarang ditemui di Indonesia. Kata kunci: Notaris, Hak Menolak, UU Jabatan Notaris, Kode Etik